Untangling the Relationship Between Mental Health and Homelessness Among a Sample of Arrestees. (May 2016) - Fox, Andrew M.; Mulvey, Philip; Katz, Charles M.; Shafer, Michael S.
Past research has focused on the intertwined relationship between homelessness, mental illness, and criminal justice. Although a well-established correlation between mental illness and homelessness has emerged, a better understanding of how this may be mediated by other prominent risk factors such as substance use or victimization is warranted. The current study uses data obtained from 3, 673 recently booked arrestees to examine these relationships. Using structural equation modeling with measured variables, the analyses indicate the relationship between mental health and homelessness to be almost entirely mediated by alcohol use, drug use, and violent victimization. Policy implications are discussed.